Assassins: The KGB's Poison Factory Ten Years On - Volodarsky, Boris (Pen & Sword Books Limited, 2020)
Cover -- Book Title -- Copyright -- Dedication -- Contents -- Acknowledgements -- Preface -- Chapter 1 Prologue -- Chapter 2 The Last Farewell -- Chapter 3 Kamera Never Dreams -- Chapter 4 A Murder in Coyoacán -- Chapter 5 Tinker Tailor Soldier Spy? No, Another Circus -- Chapter 6 Assassin Turned Professor -- Plate Section -- Chapter 7 From Russia with a Poison Gun -- Chapter 8 Road to Donbass -- Chapter 9 Of Mice and Moles -- Chapter 10 The Oligarch -- Chapter 11 A Venomous Agent -- Chapter 12 Epilogue: From the one-party terrorist state to the Putin presidency: "We'll wipe them out in the shithouse" -- Appendix I: Alexander Perepilichny: An Unexplained Death -- Appendix II: Special Tasks: Assassination Files -- Abbreviations and Acronyms -- Bibliography -- Index -- Back Cover.